EVALUASI TINGKAT KETERISIAN RUANG HENTI KHUSUS SEPEDA MOTOR DI KOTA BEKASI (STUDI KASUS: PERSIMPANGAN JL. JEND. AHMAD YANI–JL. MAYOR MADMUIN HASIBUAN–JL. KH. NOER ALI, BEKASI) - Medina, Citra Ayu; Hadi, Winoto; Anisah (LPPM, Universitas Negeri Jakarta, 2022)
The purpose of this study was to get know success or failure of Advanced Stop Lines with the parameters of the level of occupancy at St. Jend Ahmad Yani – St. Mayor Madmuin Hasibuan – St. KH Noer Ali, Bekasi. The method used in supporting the implementation of this research was by using the survey method conducted at 6 - 8 am,12 pm – 1 am and 4 am – 6 am, the data obtained is the number of motorcycles in the Advanced Stop Line area and many phases are only motorized. The analysis results obtained that Advanced Stop Line Based on Modul Pelatihan Monitoring dan Evaluasi RHK 2012 was <60%. It indicates that Advanced Stop Lines at St. Jend Ahmad Yani – St. Mayor Madmuin Hasibuan – St. KH Noer Ali, Bekasi not being an appropriate solution.